The relationship between halal food management system critical constructs implementation, operational performance and product quality - Ahmad, Anis Najiha; Ab. Rahman, Rozanah; Othman, Maizatulnisa; Che Ishak, Farah Adibah; Mohamad, Siti Fatimah; Ungku Zainal Abidin, Ungku Fatimah (Human Resource Management Academic Research Society (HRMARS), 2020)
Given the limited studies on Halal food management system, this study seeks to assess the relationship between the implementation of Halal food management system critical constructs, operational performance and product quality. A total of 163 samples collected from Halal certified SMEs manufacturers in Malaysia were used for data analysis. Data were initially subjected to exploratory factor analysis (EFA) to identify the underlying constructs. Partial least squares (PLS) was then used to examine the extent to which implementation of halal food management system critical constructs influence operational performance and product quality. The results showed that not all critical constructs were directly and positively associated with organisational performance and product quality. The lack of significant relationships between critical constructs and performance constructs are intriguing and should be an impetus for further investigations into potential contingencies and indirect associations of Halal food management system critical constructs on performance constructs. In addition, rather than a piecemeal approach, companies may need to holistically and systemically implement all the Halal food management system critical constructs.